2011
DOI: 10.1155/2011/608349
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Methylated Bismuth Compounds Produced by Intestinal Microorganisms toBacteroides thetaiotaomicron, a Member of the Physiological Intestinal Microbiota

Abstract: Methanoarchaea have an outstanding capability to methylate numerous metal(loid)s therefore producing toxic and highly mobile derivatives. Here, we report that the production of methylated bismuth species by the methanoarchaeum Methanobrevibacter smithii, a common member of the human intestine, impairs the growth of members of the beneficial intestinal microbiota at low concentrations. The bacterium Bacteroides thetaiotaomicron, which is of great importance for the welfare of the host due to its versatile diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Using an in-vitro model of the human gut microbiome, Diaz-Bone and van de Wiele [42] found that normal human intestinal bacteria metabolize environmental contaminants, turning polycyclic aromatic hydrocarbons into bioactive estrogen-like molecules and transforming metals into volatile, and sometimes toxic, products [43] that can affect the gut’s species balance and function, a condition known as dysbiosis. One study found that dysbiosis can potentially result from bismuth exposure, commonly found in cosmetics and Pepto-Bismol, when Methanobrevibacter smithii , a normal gut inhabitant, transforms bismuth into a form that is toxic to Bacteroides thetaiotaomicron, a beneficial resident that mediates infant dietary transition from breastmilk to starches, and aids the formation of the intestinal mucosal barrier that protects against pathogens [44 ▪ ]. Hence, early-life toxicant exposure could shift the microbial balance, potentially affecting both immune and microbiome development.…”
Section: External Factors and The Impact On Normal Neonatal Gutmicrobmentioning
confidence: 99%
“…Using an in-vitro model of the human gut microbiome, Diaz-Bone and van de Wiele [42] found that normal human intestinal bacteria metabolize environmental contaminants, turning polycyclic aromatic hydrocarbons into bioactive estrogen-like molecules and transforming metals into volatile, and sometimes toxic, products [43] that can affect the gut’s species balance and function, a condition known as dysbiosis. One study found that dysbiosis can potentially result from bismuth exposure, commonly found in cosmetics and Pepto-Bismol, when Methanobrevibacter smithii , a normal gut inhabitant, transforms bismuth into a form that is toxic to Bacteroides thetaiotaomicron, a beneficial resident that mediates infant dietary transition from breastmilk to starches, and aids the formation of the intestinal mucosal barrier that protects against pathogens [44 ▪ ]. Hence, early-life toxicant exposure could shift the microbial balance, potentially affecting both immune and microbiome development.…”
Section: External Factors and The Impact On Normal Neonatal Gutmicrobmentioning
confidence: 99%
“…A MIC 50 of 17-30 nM of TMBi was determined. The study by Bialek et al [45] also showed the inhibitory effects of soluble, partly methylated mono-and dimethylbismuth with a MIC 50 also in the low nM range. In contrast, the MIC 50 of CBS is four orders of magnitude higher, demonstrating the greater antibacterial effect of methylated bismuth derivatives relative to inorganic derivatives used in medical applications.…”
Section: Formation Of Toxic Methylated Bismuthmentioning
confidence: 91%
“…The formation of toxic TMBi in the human colon may also affect the physiological gut microbiota, as indicated by ex situ experiments performed by Meyer et al in 2008 and later by Bialek et al [41,45]. Both studies demonstrated growth impairment of pure cultures of Bacteroides thetaiotaomicron, a representative of the physiological gut microbiota, by TMBi.…”
Section: Formation Of Toxic Methylated Bismuthmentioning
confidence: 99%